FUNGSI MASJID BAGI MAHASISWA INDONESIA DI AUSTRALIA (STUDI KASUS DI MASJID WESTALL MELBOURNE AUSTRALIA) - Fajri Ahmad; Tomi Hendra (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2020)
This research discusses the function of mosques towards Indonesian students in Melbourne Australia. Westall Mosque owned by Indonesian congregation is located in the Melbourne City in Australia which has been established since 1997. This research used a qualitative method with a field approach. The results of this study indicate that the function of the mosque for Indonesian students studying at the Westall Mosque is to make the mosque the center of the Islamic missionary movement in the Melbourne City towards muslims in there. By doing da'wah activities such as tausiyah on Saturdays-Sundays, religious rituals during the month of Ramadan, tahsin for kids and tahsin for adults as well as being a preacher in the implementation of Friday prayers. Then the Westall Mosque is used as the glue of unity for students from Indonesia, holding a mosque open day, which is a national event in Australia which aims to visit the mosque to get to know about Islam.